PENGARUH MEDIA SOSIAL INSTAGRAM DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA KONVEKSI JERSEY WAYSPORT APPAREL JOMBANG KOTA TANGERANG SELATAN - Jiana Dwi Arianti; Mahnun Mas’adi (LAP4B, 2026)
This study aims to determine the influence of Instagram Social Media and Service Quality on consumer Purchasing Decisions at Konveksi Jersey Waysport Apparel Jombang, South Tangerang City. The research method used is a quantitative and associative approach. The number of respondents in this study was 97 people selected using a purposive sampling method. Based on the results of the partial test (t test), the Instagram Social Media variable (X1) was proven to have a positive and significant influence on Purchasing Decisions (Y), with a calculated t value of 8.172> t table 1.985, and a significance value of 0.000 <0.05. Likewise, the Service Quality variable (X2) showed a positive and significant influence on Purchasing Decisions (Y), with a calculated t value of 9.298> t table 1.985 and a significance value of 0.000 <0.05. Meanwhile, the results of the simultaneous test (F test) showed F count of 62.769 > F table 3.093, with a significance value of 0.000 < 0.05. Thus, simultaneously Instagram Social Media and Service Quality have a significant effect on consumer Purchasing Decisions. The results of this study indicate that the utilization of Instagram Social Media and improving Service Quality play an important role in driving Purchasing Decisions. Therefore, Waysport Apparel Jersey Convection is advised to continue optimizing the use of Instagram Social Media as a marketing and communication tool and improving the quality of service in serving consumers. By focusing on these two aspects, the company can be more effective in driving consumer purchasing decisions and increasing business competitiveness amidst the tight competition in the convection industry.